Potensi Air Limbah Domestik Sebagai Pasokan Air Irigasi pada Daerah Padat Penduduk dan Krisis Air - Sutriati, Armaita; Ginting, Nana Terangna (Jurnal Irigasi, 2012)
Indonesia is the country most vulnerable to food security in the face of water deficit. Java and Bali have a deficit of irrigation water since 2003. Assessment of the potential of domestic wastewater for irrigation water supply intended for alternative sources of raw water to overcome water shortage in densely populated areas are like in Java and Bali. Assessment using the method of analysis of primary and secondary data obtained from the literature. The results of the study demonstrate the potential quantity of domestic waste water in 2020 an average of about 228.12 m3/sec in Indonesia, while in Java around 132.38 m3/sec and in Bali about 3.94 m3/sec. Potential nutrients in domestic wastewater in 2020 in P. Java: Nitrogen approximately 208,740 tons / year, equivalent to 386,556 tons of urea / year; Phosphorus tons / year, equivalent to 41,748 TSP 115,967 tons / year, and Potassium 83,496 tons / year or KCl equivalent to 185,547 tons / year. The benefits of implementing policies reuse of domestic wastewater for irrigation is an effort to support sustainable agriculture as well as to supply the raw water continuously during water deficit, as well as a source of nutrients to substitute fertilizer needs. Use of domestic wastewater for irrigation can also improve soil structure and reduce the pollution load entering the water. In practice, some farmers around the Domestic Wastewater Treatment Plant in Bojongsoang and Perumnas in Cirebon have received the benefits of using domestic wastewater for irrigation, especially in the dry season. The level of difficulty of obtaining water is an important factor for the success of the re-use of domestic waste water for irrigation.